Managing the risk of fraud and misconduct [ meeting the challenges of a global, regulated and digital environment - Girgenti, Richard H.; Hedley, Timothy P. (McGraw-Hill, 2011)
A high-level, strategy-based guide to protecting anyorganization from wrongdoers within